2012
DOI: 10.1016/j.nlm.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Selective lesions of the dentate gyrus produce disruptions in place learning for adjacent spatial locations

Abstract: The hippocampus (HPP) plays a known role in learning novel spatial information. More specifically, the dentate gyrus (DG) hippocampal subregion is thought to support pattern separation, a mechanism for encoding and separating spatially similar events into distinct representations. Several studies have shown that lesions of the dorsal DG (dDG) in rodents result in inefficient spatial pattern separation for working memory; however, it is unclear whether selective dDG lesions disrupt spatial pattern separation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 46 publications
(82 reference statements)
6
78
0
Order By: Relevance
“…The discrimination task we used has been previously shown to rely on hippocampal function (Gilbert et al 1998), and more specifically on the dentate gyrus (Gilbert et al 2001). Furthermore, dentate gyrus lesions in young rats impair performance on spatial working memory tests (Xavier et al 1999;Morris et al 2012). Thus, lesion studies in rats suggest that age-related deficits in discriminating between spatial stimuli could be linked to age-related changes in hippocampal function, and particularly to the dentate gyrus.…”
Section: Spatial Memory and Spatial Discrimination Abilities: Implicamentioning
confidence: 99%
See 1 more Smart Citation
“…The discrimination task we used has been previously shown to rely on hippocampal function (Gilbert et al 1998), and more specifically on the dentate gyrus (Gilbert et al 2001). Furthermore, dentate gyrus lesions in young rats impair performance on spatial working memory tests (Xavier et al 1999;Morris et al 2012). Thus, lesion studies in rats suggest that age-related deficits in discriminating between spatial stimuli could be linked to age-related changes in hippocampal function, and particularly to the dentate gyrus.…”
Section: Spatial Memory and Spatial Discrimination Abilities: Implicamentioning
confidence: 99%
“…Both spatial memory and spatial discrimination require intact hippocampal function (Schenk and Morris 1985;Xavier et al 1999;Gilbert et al 1998Gilbert et al , 2001Gilbert and Kesner 2006;Morris et al 2012), and age-related differences in hippocampal-dependent memory function have recently been linked to differences in discrimination abilities in humans (Stark et al 2013;Reagh et al 2014Reagh et al , 2016, as well as in rats (LaSarge et al 2007). We therefore sought to determine whether spatial memory performance on the water maze task was correlated with spatial discrimination performance across our cohort of young and aged rats.…”
Section: Spatial Memory and Spatial Discrimination Abilities Are Notmentioning
confidence: 99%
“…As described above, a direct projection from the entorhinal cortex to CA1 is thought to be able to subserve basic allocentric spatial processing. In contrast, computational models and a number of in vivo studies support the hypothesis that the dentate gyrus, together with its connections with CA3, subserve a process known as pattern separation (Bakker, Kirwan, Miller, & Stark, 2008;Brun, Leutgeb, et al, 2008;Gilbert, Kesner, & DeCoteau, 1998;Gilbert, Kesner, & Lee, 2001;Kesner, 2007;Leutgeb, Leutgeb, Moser, & Moser, 2007;Nakashiba, Young, McHugh, Buhl, & Tonegawa, 2008;Nakazawa et al, 2002), which might be necessary to discriminate individual items, episodes or spatial locations that are very similar or close to one another (Brun, Leutgeb, et al, 2008;Kesner, 2007;Morris, Churchwell, Kesner, & Gilbert, 2012;Rolls, 2008). In accordance with this hypothesis, studies have shown that disrupting the CA3 input to CA1 results in decreased spatial tuning of CA1 place cells (Brun et al, 2002;Nakashiba et al, 2008), thus suggesting the necessity of the main trisynaptic hippocampal pathway (i.e., entorhinal cortex to dentate gyrus, dentate gyrus to CA3, CA3 to CA1) for maintaining high-resolution spatial discrimination (i.e., spatial pattern separation).…”
Section: Improved Allocentric Spatial Processing After 2 Years Of Agementioning
confidence: 99%
“…There are two likely candidate sources for rate remapping: the DG and the LEC. The DG is sensitive to subtle changes in environmental context, as revealed by the morph-box paradigm , and several studies have shown that animals with DG lesions are impaired when making place discriminations (Gilbert et al 2001;Goodrich-Hunsaker et al 2008;Morris et al 2012;Kesner 2013) and context discriminations (Lee et al 2004b;McHugh et al 2007;Tronel et al 2012;Kheirbek et al 2012;Nakashiba et al 2012). For example, in a fear conditioning paradigm, animals with DG lesions failed to distinguish between ambiguous environments (one box in which they were fear conditioned and a second similar but unfamiliar box that differs from the first only in some nonspatial cue, like color) (McHugh et al 2007).…”
Section: The Responses Of Spatial Cells To Changes In the Environmentmentioning
confidence: 99%